LGI-1 encephalopathy following ChAdOx1 nCov-19 vaccination. - Garibashvili, Tamara; Heckmann, Josef Georg (Neurological Research and Practice, 2022)
A 71-year-old male patient was diagnosed with LGI1 encephalopathy 4 weeks following a first ChAdOx1 nCov-19 vaccination. Extensive work-up including analysis of CSF and PET examination did not reveal a tangible cause so that a vaccine-associated encephalopathy was considered as differential diagnosis. Under steroid treatment, the faciobrachial dystonic seizures subsided.
EVALuna2:530412